Social psychology - Myers, David G. (New York : McGraw Hill Education, 1987)
In all of history, human social behavior has been scientifically studied in only one century. That century is ours. Considering that we have barely begun, the results are, I believe, gratifying. Social psychologists have gleaned significant insights into belief and illusion, love and hate, conformity and independence. Although much mystery remains, we can now offer partial answers to such questions as: Will people act in new and better ways if we can first persuade them to adopt new attitudes? Do males and females differ? How? Why? When are people most likely to help another? What kindles social conflict, and what steps can be taken to transform closed fists into open arms? Learning even tentative answers to such questions can stimulate our thinking about social behavior. Moreover, becoming sensitive to the social forces at work upon us can help free us from susceptibility to unwanted manipulation. I hope that such will be among the benefits of studying social psychology.
Social Thinking -- Social Influence -- Social Relations.
Includes bibliographical references and index.
Keywords: SOCIAL PSYCHOLOGY